Stochastic model and method of optimization of operating modes groups of artesian wells in water supply systems - Tevyashev, Andriy; Matvienko, Olga; Nikitenko, Gleb (Transfer of innovative technologies, 2021)
Water supply of large cities is carried out, as a rule, from open reservoirs - lakes, reservoirs, large rivers, ie from sources with significant water reserves. In this case, the water supply scheme includes: pumping stations of the first rise, which take water directly from the water; water treatment system (purification); pumping stations of the second and third rise, pumping clean water over long distances and supplying it to settlements [1]. If the settlement is located in an area where there are no large open water sources, or the geographical location of the settlement allows the use of groundwater, in which case artesian wells are used as a source of water supply. Usually small settlements are supplied with water from artesian wells. Artesian wells are widely used for water supply of villages, industrial water supply, for irrigation (irrigation systems), in the mining industry, to reduce the level of groundwater. The advantage of using artesian wells to supply the population with drinking water is that the water is extracted from great depths and purified using natural filters [2]. Thus, the cost of water treatment is significantly reduced. The disadvantage of using artesian wells is usually low productivity of the well, the strong dependence of water volumes in the well on climatic and weather conditions, depletion of the well as a result of large-scale construction or extraction of natural minerals such as shale gas [3].